2017
DOI: 10.1007/s00253-017-8212-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium lauryl ether sulfate (SLES) degradation by nitrate-reducing bacteria

Abstract: The surfactant sodium lauryl ether sulfate (SLES) is widely used in the composition of detergents and frequently ends up in wastewater treatment plants (WWTPs). While aerobic SLES degradation is well studied, little is known about the fate of this compound in anoxic environments, such as denitrification tanks of WWTPs, nor about the bacteria involved in the anoxic biodegradation. Here, we used SLES as sole carbon and energy source, at concentrations ranging from 50 to 1000 mg L−1, to enrich and isolate nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…The fact that a bacterial consortium and not a single species was isolated using SLES as the only carbon source is in line with what other authors found in wastewaters (Khleifat, 2006;Paulo et al, 2017;Fedeila et al, 2018). However, the bacterial consortia isolated in these works were able to degrade only 50% of SLES in 5 days at an initial concentration of 250 mg/L (Fedeila et al, 2018), 86% in 21 days at an initial concentration of 10 mg/L (Paulo et al, 2017) and 100% in 4-6 days at an initial concentration of 3 g/L (Khleifat, 2006), respectively. Recent studies report SLES as a biodegradable compound in foaming agent conditioned soil from tunnel excavation sites, with half lives of 6-9 days for initial SLES concentrations of 70-100 mg/kg (Barra Caracciolo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that a bacterial consortium and not a single species was isolated using SLES as the only carbon source is in line with what other authors found in wastewaters (Khleifat, 2006;Paulo et al, 2017;Fedeila et al, 2018). However, the bacterial consortia isolated in these works were able to degrade only 50% of SLES in 5 days at an initial concentration of 250 mg/L (Fedeila et al, 2018), 86% in 21 days at an initial concentration of 10 mg/L (Paulo et al, 2017) and 100% in 4-6 days at an initial concentration of 3 g/L (Khleifat, 2006), respectively. Recent studies report SLES as a biodegradable compound in foaming agent conditioned soil from tunnel excavation sites, with half lives of 6-9 days for initial SLES concentrations of 70-100 mg/kg (Barra Caracciolo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Another possible mechanism is ester cleavage, which directly causes the split of the sulfate, before the degradation of the carbon chain (Hales et al, 1986). SLES is a biodegradable compound and some microbial consortia (a group of two or more different species working together) able to degrade it have been isolated from wastewater in laboratory cultures, such as the consortium comprising the genera Pseudomonas and Aeromonas (Paulo et al, 2017) and the consortium comprising the genera Serratia, Enterobacter, and Alcaligenes (Fedeila et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…strain Des1 (38,39), Pseudomonas sp. strain SC25A (40), and P. nitroreducens (41) revealed that degradation starts with cleavage of the ether bonds, but cleavage of the sulfate ester bond has also been shown to occur concomitantly to ether cleavage in some of these strains (41,42). However, in strain PAO1, the sdsB1 deletion mutant, which does not express the alkylsulfatase SdsA1, could not no longer grow with SLES, indicating that SLES degradation is compulsively initiated by sulfate ester hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The surfactant that has a lot of application is anionic surfactant. It can be used as food additive, emulsifier agent at drug industry and also detergent (Paulo, 2017). Since the anionic surfactant has a lot of applications, it needs the development to s anionic qualified produce urfactant.…”
Section: Introductionmentioning
confidence: 99%